2008
DOI: 10.3168/jds.2008-1097
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alveolar and Cisternal Compartments Induced by Milking Interval in the Udder of Dairy Ewes

Abstract: The aim of this work was to evaluate the effects of milking interval (4, 8, 12, 16, 20, and 24 h) on cisternal size and milk partitioning (cisternal and alveolar) in the udders of dairy ewes. Twenty-four dairy ewes (Manchega, n = 12; Lacaune, n = 12) were used in a 2-wk experiment during mid-lactation. Cisternal and alveolar milk yields were measured and milk samples from each udder fraction were collected for analysis. Cisternal milk was obtained after i.v. injection of an oxytocin receptor antagonist, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 20 publications
4
31
0
7
Order By: Relevance
“…CMY and AMY are positively correlated with the milk-yielding parameters (TM, r 00.99 and r00.86; HP, r00.53 and r00.50, for cisternal and alveolar milk quantity, respectively). These results are in concordance with Castillo et al (2008), who found these correlations in dairy ewes (TM at 16 h, r 00.89 and r00.70; TM at 24 h, r00.93 and r00.68, for cisternal and alveolar milk, respectively). The percentages of the milk partitioning (CMP and AMP) have no correlation with the milk-yielding parameters.…”
Section: Udder Morphologic Measuressupporting
confidence: 81%
See 2 more Smart Citations
“…CMY and AMY are positively correlated with the milk-yielding parameters (TM, r 00.99 and r00.86; HP, r00.53 and r00.50, for cisternal and alveolar milk quantity, respectively). These results are in concordance with Castillo et al (2008), who found these correlations in dairy ewes (TM at 16 h, r 00.89 and r00.70; TM at 24 h, r00.93 and r00.68, for cisternal and alveolar milk, respectively). The percentages of the milk partitioning (CMP and AMP) have no correlation with the milk-yielding parameters.…”
Section: Udder Morphologic Measuressupporting
confidence: 81%
“…The percentages of the milk partitioning (CMP and AMP) have no correlation with the milk-yielding parameters. The percentage of fat contained in the milk is positively correlated with AMP due to the alveolar milk being richer in fat Ayadi et al 2004;Castillo et al 2008). These percentages present correlations with the main tissue components (secretory tissue, r00.48, connective tissue, r0 (0.54, for alveolar milk percentage).…”
Section: Udder Morphologic Measuresmentioning
confidence: 57%
See 1 more Smart Citation
“…In our conditions, breed Lacaune had almost double cisternal volume than Tsigai and Improved Valachian (Milerski et al, 2006). High-yielding Lacaune ewes presented greater cisternal milk percentages and more cisternal milk than mediumyielding ewes (Castillo et al, 2008).…”
Section: Residual Milk Volumementioning
confidence: 55%
“…Cistern size is an important factor in determining the milkability (L abussière, 1988; Marnet and McKusick, 2001) and the adequate interval between milkings (Knight and Dewhurst, 1994;Salama et al, 2003). Animals that store a large proportion of milk in the gland cistern produce more milk, and are more able to tolerate extended milking intervals (Salama et al, 2004;Castillo et al, 2008b;Castillo et al, 2009). Moreover, cistern size plays an important role in controlling milk secretion because when the cistern reaches its full capacity, physical pressure and FIL concentration within alveoli are increased (Wilde et al, 1996).…”
Section: Introductionmentioning
confidence: 99%